Pengaruh Academic Burnout dan Academic Engagament Terhadap School Well-Being Santri Pesantren - Oktia, Vanika (Utan Kayu Publishing, 2022)
Pesantren is a residence or a dormitory for the students to conduct religious education and other subjects. Evaluation of the school condition and the lives of students in his school environment can be called as school well-being. The various activities undertaken by the students can cause physical and psychological fatigue, known as academic burnout. One way to improve the school's well-being possessed by students is to increase the academic engagement or involvement of students in activities at the dormitory. The purpose of this study was to determine the influence of academic burnout and engagement toward school well-being in boarding school students. The hypothesis was tested by using a multiple linear regression model. Based on the results of the regression test showed that there is a significant influence of academic burnout and academic engagement toward school well-being of boarding school students (R2 = 0.239) indicating that the contribution of academic burnout and engagement toward school well-being in boarding school students was 23.9%, while the remaining 76.1% is influenced by other factors. The results of the partial test (t test) explained that academic burnout has a significant negative impact on the school well-being (t = -4.151 and p = 0.000), and academic engagement also has a significant positive impact on the school well-being (t = 5.477 and p = 0.000). The research hypothesis is proven.